2004
DOI: 10.1210/jc.2004-0190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pioglitazone on Circulating Adipocytokine Levels and Insulin Sensitivity in Type 2 Diabetic Patients

Abstract: We examined the effect of pioglitazone (PIO) on circulating adipocytokine levels to elucidate the mechanisms by which thiazolidinediones improve insulin resistance in type 2 diabetes mellitus (T2DM). Twenty-three subjects with T2DM (age 54 +/- 2 yr, body mass index 29 +/- 1 kg/m(2)) were randomly assigned to receive placebo (n = 11) or PIO, 45 mg/d (n = 12), for 4 months. Before and after treatment, subjects received a 75-g oral glucose tolerance test (OGTT); euglycemic insulin clamp (40 mU/m(2).min) with 3-(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
157
1
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(194 citation statements)
references
References 60 publications
28
157
1
8
Order By: Relevance
“…Compounds that increase endogenous adiponectin levels may be proven to have beneficial effects on treatment of depression. Administration of peroxisome proliferator-activated receptor-Îł (PPARÎł) agonists increases plasma levels of adiponectin by two-to threefold (46)(47)(48)(49). Interestingly, it has been recently reported that PPARÎł agonists, i.e., pioglitazone and rosiglitazone, produce antidepressant effects (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Compounds that increase endogenous adiponectin levels may be proven to have beneficial effects on treatment of depression. Administration of peroxisome proliferator-activated receptor-Îł (PPARÎł) agonists increases plasma levels of adiponectin by two-to threefold (46)(47)(48)(49). Interestingly, it has been recently reported that PPARÎł agonists, i.e., pioglitazone and rosiglitazone, produce antidepressant effects (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pioglitazone has been shown to reduce neointimal thickening after endothelial injury in animal models of atherosclerosis 10) . Furthermore, pioglitazone can modify systemic inflammatory and coagulation markers 8,9) . Recently, pioglitazone was found to modify the progression of carotid atherosclerosis induced by various genetic risk factors 28) .…”
Section: Discussionmentioning
confidence: 99%
“…It acts by increasing insulin sensitivity, mediating favorable effects on blood glucose levels and lipid profile 7) . In addition to these metabolic actions, pioglitazone has beneficial effects on systemic inflammatory and coagulation markers, and endothelial cell function 8,9) . Thus, the overall pattern of changes induced by pioglitazone suggests a general improvement of various risk factors for atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…mRNA for VCAM-1 and scavenger receptor class A were significantly reduced in lesions from these mice [50]. Interestingly, PPARÎł agonists are known to promote adipocyte differentiation and also to increase adiponectin transcription and serum levels [51]. However, clinical data suggest that PPARÎł agonists may rather promote cardiovascular adverse events than be atheroprotective [30].…”
Section: Adiponectin and Other Adipokinesmentioning
confidence: 96%